2004
DOI: 10.1002/jcb.20094
|View full text |Cite
|
Sign up to set email alerts
|

G protein mediated signaling pathways in lysophospholipid induced cell proliferation and survival

Abstract: Agonist activation of a subset of G protein coupled receptors (GPCRs) stimulates cell proliferation, mimicking the better known effects of tyrosine kinase growth factors. Cell survival or apoptosis is also regulated via pathways initiated by stimulation of these same GPCRs. This review focuses on aspects of signaling by the lysophospholipid mediators, lysophosphatidic acid (LPA), and sphingosine 1 phosphate (S1P), which make these agonists uniquely capable of modulating cell growth and survival. The general fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
178
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(184 citation statements)
references
References 118 publications
(119 reference statements)
5
178
1
Order By: Relevance
“…Experiments using receptor antagonists point to S1P 1 /S1P 3 being involved. Activation of PI3K and p42/44 MAPK are two pathways known to be activated by S1P (31), with the notion that these pathways also promote cell survival. Kang et al reported up-regulation of cFLIP and phosphorylation of Bad downstream of PI3K/Akt signaling (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments using receptor antagonists point to S1P 1 /S1P 3 being involved. Activation of PI3K and p42/44 MAPK are two pathways known to be activated by S1P (31), with the notion that these pathways also promote cell survival. Kang et al reported up-regulation of cFLIP and phosphorylation of Bad downstream of PI3K/Akt signaling (45).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, S1P is exported from the cell by members of the ATP-binding cassette transporter family. Once secreted, S1P binds to one of its five G-proteincoupled receptors (S1P 1 -S1P 1 ), activating downstream pathways such as p38 MAPK, p42/44 MAPK, PI3K, c-Jun NH 2 -terminal kinase, or Ca 2+ signaling (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…LPA-mediated signalling via Gα 12/13 and activation of the signalling pathways involving RhoA, Rhokinase, ROCK and Ras appear to be involved in NP (Inoue et al, 2004;Radeff-Huang et al, 2004;Ueda, 2006). Inhibition of Rho signalling pathways by Clostridium botulinum C3 exoenzyme (BoTXC3) or the antagonist Y-27632 (see Table 1), prior to peripheral nerve injury, blocks hyperalgesia and nociceptive responses in mice (Ahn et al, 2009;Inoue et al, 2004;Inoue et al, 2006).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Since Edg receptors affect cell motility via the Gi pathway [13,14], we next tested the dependence of gelatinase activity on Gi using its specific inhibitor, PTX. We chose also to evaluate OVCA 429, another EOC cell line that does not invade well through matrigel, as a means of comparison.…”
Section: S1p Effects On Gelatinase Activity In Dov 13 and Ovca 429 Cementioning
confidence: 99%
“…We have recently shown that S1P regulates transcription and surface presentation of its own receptors [12]. The G proteins that mediate the biologic effects of S1P are associated with particular Edg's, and pathways have been identified to all known S1P receptors through coupled G-Proteins, including the Gi subgroup [13]. Further downstream is Rac, a small GTP binding protein of the Rho family.…”
Section: Introductionmentioning
confidence: 99%